Promoción de la Participación de Mujeres en Ingeniería: Construcción de Vocaciones, Influencia Escolar y Familiar, y Buenas Prácticas para la Equidad de Género en STEM - Redin Villareal, Yesica; Macias Jimenez, Geny Andrea; Daza Caicedo, Alicia; Martinez Daraviña, Lina Marcela; Mina Cordoba, Jhoan Alexis; Neira Parra, Jacqueline (LACCEI, 2024)
This literature review explores the critical importance of involving women in engineering, highlighting the construction of vocational interests and the awakening of enthusiasm for engineering among young women. It examines the significant influence of familial and educational environments in shaping these interests and discusses various models for discovering vocational inclinations towards STEM fields. The review also celebrates pioneering women in STEM and the role of female mentors who have paved the way for future generations. Additionally, it assesses the progress of women in the workforce, focusing on their performance across various practices. Finally, the review outlines best practices for promoting gender equity in STEM areas, emphasizing the need for inclusive policies and supportive environments to foster diversity and inclusion. This comprehensive overview underscores the multifaceted efforts required to support and advance the participation of women in engineering and other STEM disciplines.